Cognitive impairment in psychiatric diseases: Biomarkers of diagnosis, treatment, and prevention - Wang, Yafen; Meng, Weicheng; Liu, Zhixin; An, Qunxing; Hu, Xingbin (Frontiers in Cellular Neuroscience, 2022)
Psychiatric diseases, such as schizophrenia, bipolar disorder, autism spectrum disorder, and major depressive disorder, place a huge health burden on society. Cognitive impairment is one of the core characteristics of psychiatric disorders and a vital determinant of social function and disease recurrence in patients. This review thus aims to explore the underlying molecular mechanisms of cognitive impairment in major psychiatric disorders and identify valuable biomarkers for diagnosis, treatment and prevention of patients.